2013
DOI: 10.1002/iub.1134
|View full text |Cite
|
Sign up to set email alerts
|

Rotating proton pumping ATPases: Subunit/subunit interactions and thermodynamics

Abstract: In this article, we discuss single molecule observation of rotational catalysis by E. coli ATP synthase (F-ATPase) using small gold beads. Studies involving a low viscous drag probe showed the stochastic properties of the enzyme in alternating catalytically active and inhibited states. The importance of subunit interaction between the rotor and the stator, and thermodynamics of the catalysis are also discussed. ''Single Molecule Enzymology'' is a new trend for understanding enzyme mechanisms in biochemistry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6][7]. It is composed of membrane extrinsic catalytic sector F 1 (␣ 3 ␤ 3 ␥␦⑀) and trans-membrane proton pathway sector F 0 (ab 2 stator and c-ring formed from multiple c subunits) (5)(6)(7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7]. It is composed of membrane extrinsic catalytic sector F 1 (␣ 3 ␤ 3 ␥␦⑀) and trans-membrane proton pathway sector F 0 (ab 2 stator and c-ring formed from multiple c subunits) (5)(6)(7).…”
mentioning
confidence: 99%
“…We concluded that ATP is hydrolyzed during the short pauses (ϳ0.2 ms), which are thus defined as "catalytic dwells" (9). The 120°rotation steps are further divided into 40°and 80°rotation steps, and the short pause between the two substeps corresponds to the ATP-binding dwell (ATP-waiting dwell), during which ATP binds to one of the three ␤ subunits, and ADP is released from another ␤ subunit (6,7,9,12).…”
mentioning
confidence: 99%
“…Studies have shown that ATP5D can also act as a potentially important cell-signaling molecule. ATP5D binds to α , β , γ , delta, and epsilon subunits to form the catalytic core (F1) of mitochondrial ATP synthase [ 39 , 40 ]. Its ability to interact with other subunits within the multiprotein complex suggests that it may also function as a scaffold protein.…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments, a magnetic bead was attached to the subunit γ , which was controlled by an external magnetic field to first force the backward (clockwise) rotation of F1, leading to ATP synthesis. When the magnetic field was switched off, the F1 molecule underwent anticlockwise rotation at a speed proportional to the amount of synthesized ATP (Rondelez et al 2005;Nakanishi-Matsui et al 2013). A further technical sophistication used a sub-millisecond resolution camera to detect the rotation of gold beads attached to the γ subunit of the α3β3γ subcomplex along with fluorescence changes of an ATP hydrolysable analog.…”
Section: Rotational Catalysismentioning
confidence: 99%